APPLIED DECORATIVE ART AND ITS VARIETIES: METHODOLOGICAL, CULTURAL AND TECHNOLOGICAL FOUNDATIONS - Ergasheva Orifakhon (The Conference Hub, 2025)
This scholarly article provides a comprehensive and multidisciplinary examination of applied decorative art as a complex cultural, aesthetic, technological, and anthropological phenomenon that has played a central role in shaping human civilization’s visual identity and material culture. Grounded in theoretical frameworks drawn from art history, ethnography, cultural semiotics, material science, and contemporary design methodology, the study analyzes the structural, functional, symbolic, and communicative dimensions of applied decorative art within both traditional and modern contexts. Employing an IMRaD structure, the research synthesizes historical evidence, comparative stylistic analysis, and interpretive methodologies to elucidate the evolution of various branches of applied decorative art—including ceramics, woodcarving, metalworking, textile art, ornamental design, calligraphic ornamentation, ganch carving, jewelry, architectural decoration, and contemporary hybrid forms—while exploring their methodological foundation, artistic principles, and socio-cultural significance. Special attention is given to how decorative art operates simultaneously as craftsmanship, cultural transmission, identity formation, and aesthetic philosophy, and how its varieties reflect the technological innovations, worldview patterns, and aesthetic sensibilities of different civilizations. The study concludes that applied decorative art remains a dynamically evolving system whose epistemological value, cultural resilience, and methodological richness continue to influence modern art education, design thinking, material culture studies, and creative industries
Keywords: Applied decorative art, ornamentation, material culture, methodology, aesthetics, cultural heritage, design, craftsmanship, semiotics, artistic technology, traditional art, visual identity, stylistic evolution.